BIOTECHNOLOGY OF USING WEEDS AS PROMISING BIOLOGICAL OBJECTS - Андрієвська, Євгенія; Самарська, Софія; Шпаков, Олексій (Modern engineering and innovative technologies, 2024)
The paper discusses the problem of weeds, which cause huge economic and environmental damage around the world. It is noted that the study of weed genomes has become a key area in understanding their biology and evolution, which opens up new opportunities